2000
DOI: 10.1061/(asce)1084-0702(2000)5:4(331)
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Reduction in Load Capacity of Highway Bridges with Age

Abstract: Bridge management systems focus on optimizing the life-cycle cost of preservation and improvement activities in a network of structures. Pontis, the predominant bridge management system currently implemented in the United States, considers load-carrying capacity as static during an incremental benefit-cost approach. Including consideration of load-carrying capacity, deterioration may enhance this model. To accomplish this goal, a method to relate load-carrying capacity to physical bridge deterioration using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Markov chains are found to be a useful tool for stochastic modelling of condition state evolution of a system with time [11,12,[36][37][38][39]. Using data on bridge superstructure condition rating from United States and Hungary, Chase and Gáspár [12] have shown that predictions on condition state using MC are in good agreement with the observed condition states. Therefore, in the present study, MC modelling is used for the condition evolution of the bridge girder with time.…”
Section: Stochastic Modelling Of the Condition State Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markov chains are found to be a useful tool for stochastic modelling of condition state evolution of a system with time [11,12,[36][37][38][39]. Using data on bridge superstructure condition rating from United States and Hungary, Chase and Gáspár [12] have shown that predictions on condition state using MC are in good agreement with the observed condition states. Therefore, in the present study, MC modelling is used for the condition evolution of the bridge girder with time.…”
Section: Stochastic Modelling Of the Condition State Evolutionmentioning
confidence: 99%
“…The stochastic evolution of condition of the RC *For correspondence bridge girder with time is modelled using a Markov chain (MC) model. Use of homogeneous MC models for modeling evolution of damage with time in bridge girders/ bridges has been proposed by various researchers [10][11][12]. However, the state transition probabilities from one fixed condition state to another need to be considered as a function of time.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst not exhaustive, examples of applied research using MDA include: evaluation of contractor creditworthiness and supplier's debt collection method (Nicholas, 2000); hydraulic conductivity of soils (Boadu, 2000); highway bridges load capacity reduction with age (Chase and Gaspar, 2000); estimation of earthmoving productivity (Smith, 1999); assessment of hoisting times of tower cranes (Leung and Tam, 1999); allocation of construction planning resources (Faniran et al, 1999); analysing highway storm water loads (Irish et al, 1998); traffic flow forecasting (Smith and Demetsky, 1997); and prediction of land subsidence due to use of ground water (Mizumura, 1994).…”
Section: Theory Of Multivariate Discriminant Analysismentioning
confidence: 99%
“…An in-depth study of bridge deterioration also involved regression models built using the NBI data coupled with geographical information systems (GIS) data on environmental and hazardous conditions that bridges are exposed to depending on their locations (Chase et al 1999). The two commonly used methods (regression and Markov models) have also been combined to analyze NBI data in the past (Chase and Gaspar 2000). The two commonly used methods (regression and Markov models) have also been combined to analyze NBI data in the past (Chase and Gaspar 2000).…”
Section: Introductionmentioning
confidence: 99%